2016
DOI: 10.3389/fpls.2016.01867
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Candidate Genes Involved in Carotenoid Biosynthesis in Chickpea Seeds

Abstract: Plant carotenoids have a key role in preventing various diseases in human because of their antioxidant and provitamin A properties. Chickpea is a good source of carotenoid among legumes and its diverse germplasm and genome accessibility makes it a good model for carotenogenesis studies. The structure, location, and copy numbers of genes involved in carotenoid biosynthesis were retrieved from the chickpea genome. The majority of the single nucleotide polymorphism (SNPs) within these genes across five diverse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 97 publications
(129 reference statements)
1
28
1
Order By: Relevance
“…Carotenoids may act as a supplement to the declining flavonoid/anthocyanin protection system and may be consumed subsequently in the leaf color change process because carotenoids in green leaves help ensure efficient photosynthesis, scavenge various reactive oxygen species, 54 and protect chlorophylls from photooxidation. 55 In addition, carotenoids can also function as precursors for apocarotenoids such as the plant hormone abscisic acid, 54 , 56 which is essential for plant growth, development, and antioxidant capacity. 57 59 In short, enhanced carotenoid biosynthesis contributed to maintaining the chlorophyll level, which resulted in the green leaf coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids may act as a supplement to the declining flavonoid/anthocyanin protection system and may be consumed subsequently in the leaf color change process because carotenoids in green leaves help ensure efficient photosynthesis, scavenge various reactive oxygen species, 54 and protect chlorophylls from photooxidation. 55 In addition, carotenoids can also function as precursors for apocarotenoids such as the plant hormone abscisic acid, 54 , 56 which is essential for plant growth, development, and antioxidant capacity. 57 59 In short, enhanced carotenoid biosynthesis contributed to maintaining the chlorophyll level, which resulted in the green leaf coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Pea and chickpea accessions with high carotenoid concentration that can be utilized in future breeding were identified. In five chickpea cultivars with different cotyledon colors, total carotenoid concentration varied from 22 µg g −1 (yellow cotyledon kabuli) to 44 µg g −1 (green cotyledon desi), with lutein and zeaxanthin as major components [187]. In a recent study, a wide range of total carotenoid concentration was observed in three F 2 populations developed by crossing cultivars with different cotyledon and seed coat colors, CDC Jade X CDC Frontier (14.9-58.1 µg g −1 ), CDC Cory X CDC Jade (1.9-77.6 µg g −1 ), and ICC4475 X CDC Jade (21.6-83.7 µg g −1 ) [188].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Previously, four QTLs for beta-carotene concentration and a single QTL for lutein concentration were detected in chickpeas [183] (Table 1). Using a GWAS, Rezaei et al [187] identified 32 candidate genes involved in isoprenoid and carotenoid pathways across all eight chromosomes of chickpeas. They observed positive correlation between the expression of genes of carotenoid biosynthesis with various carotenoid components.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Carotenoids comprise 40 carbon isoprenoids that are usually involved in yelloworange coloration (Hirschberg 2001). To date, almost all of the genes related to carotenoid biosynthesis have been characterized (Pandurangaiah et al 2016, Rezaei et al 2016, Yang et al 2016. However, there are few genetic data involved in carotenoid pathways of Strelitzia reginae.…”
Section: Introductionmentioning
confidence: 99%